Shaker Exercise untuk Meningkatkan Refleks Menelan Pada Pasien Stroke : Rapid Evidence Review - Sandra Pebrianti; Iwan Shalahuddin; Bambang Aditya Nugraha (Malahayati Nursing Journal, 2025)
ABSTRACT Dysphagia is a disorder that causes difficulty chewing and swallowing food. This condition can lead to very serious complications such as pneumonia, aspiration, dehydration, and malnutrition, and can sometimes lead to death. One form of intervention that can be done to speed up recovery and minimize complications due to dysphagia is to do swallowing exercises. To determine the effectiveness of Shaker Exercise in improving swallowing reflexes in Stroke Patients. This rapid review uses a literature search strategy with PICOT framework analysis. The inclusion criteria in this rapid review include Full text, English, RCT, Clinical trial, Quasi experiment, control study, Dyspagia patients after having a stroke, articles for 2014-2024. The results of three databases, namely PubMed, EBSCO, and Scopus, found 6 literature that was thoroughly analyzed to be used as Evidence Based Practice (EBP). From the 6 articles analyzed, it was identified that shaker exercises are one of the interventions that can be given to dysphagia patients after having a stroke. Several articles explain the duration of the shaker training technique which varies from 30-60 minutes. Some articles also combine or compare these exercises with other interventions. Based on the results of the literature review from the 6 articles that have been obtained, this shaker exercise is effective and can be beneficial for patients if done regularly and regularly. Shaker exercises provide better results in improving the quality of life and swallowing function in patients. Nurses and other health workers need to consider interventions that are appropriate to the patient's needs and the situation of the health care condition Keywords: Shaker Exercise, Swallow Reflex, Stroke  ABSTRAK Disfagia adalah gangguan yang menyebabkan kesulitan mengunyah dan menelan makanan. Kondisi ini dapat menyebabkan komplikasi yang sangat serius seperti pneumonia, aspirasi, dehidrasi, dan malnutrisi, dan kadang-kadang dapat menyebabkan kematian. Salah satu bentuk intervensi yang dapat dilakukan untuk mempercepatkesembuhan dan meminimalkan komplikasi akibat disfagia adalah dengan melakukan latihan menelan. Untuk mengetahui efektivitas Shaker Exercise dalam meningkatkan refleks menelan pada Pasien Stroke. Rapid review ini menggunakan strategi pencarian literatur dengan analisis framework PICOT. Kriteria Inklusi pada rapid review ini diantaranya Full text, Berbahasa inggris, RCT, Clinical trial, Quasi experimen, control study, Pasien dispagia setelah mengalami Stroke, artikel tahun 2014-2024. Hasil dari tiga database yaitu PubMed, EBSCO, dan Scopus ditemukan 6 literatur yang dianalisis secara menyeluruh untuk digunakan sebagai Evidence Based Practice (EBP). Dari 6 artikel yang dianalisis, diidentifikasi bahwa latihan shaker menjadi salah satu intervensi yang dapat diberikan pada pasien disfagia setelah mengalami stroke. Beberapa artikel menjelaskan durasi teknik latihan shaker yang bervariasi yaitu 30-60 menit. Beberapa artikel juga mengkombinasi atau membandingkan latihan ini dengan intervensi lain. Berdasarkan hasil literatur review dari ke-6 artikel yang telah didapatkan bahwa latihan shaker ini efektif dan dapat bermanfaat untuk pasien apabila dilakukan dengan rutin dan teratur. Latihan shaker memberikan hasil yang lebih baik dalam meningkatkan kualitas hidup dan fungsi menelan pada pasien. Perawat dan tenaga kesehatan lain perlu mempertimbangkan intervensi yang sesuai dengan kebutuhan pasien dan situasi kondisi pelayanan kesehatan Kata Kunci: Shaker Exercise, Refleks Menelan, Stroke